Housing Financialization in the Global South: In Search of a Comparative Framework. Issue 4 (3rd July 2020) - Fernandez, Rodrigo; Aalbers, Manuel B.
ABSTRACT: The financialization of housing in the Global South (GS) and peripheries of the Global North (GN) develops in different ways than in the GN because the mechanisms underlying and pushing financialization are fundamentally different. We argue that subordinated financialization in the GS is the contemporary form of uneven and combined development, shaped by the financialization of the GN. The recycling of GN excess liquidity in countries lower in the global money hierarchy has contributed to the growth of mortgage lending in the GS and peripheries of GN. With the macrocomparative perspective in our article we provide a framework to rethink the relations between GN and GS in shaping distinct patterns of uneven and combined financialization, but also to rethink the varieties of capitalism and residential capitalism approaches. In the GS we can distinguish between at least two additional types: state-led market economies and less-financialized market economies.